Empathy levels and its relationship with various independent factors: a web-based cross-sectional study amongst medical students - Rawat, Ranu; Singh, Parmal (International Journal Of Community Medicine And Public Health, 2020)
Background: Empathy is a critical construct in the context of the doctor patient relationship. Very few studies in India have previously assessed clinical empathy explicitly in medical students. The present study aimed to estimate and compare the empathy scores of the medical students with various independent factors and to determine the correlation between empathy scores and age of participants. Methods: A web based cross-sectional study was undertaken using a partly self-designed and partly pre-designed Jefferson scale of physician empathy (JSPE) questionnaire for data collection. Results: The mean empathy score of the students was found to be 98.79±12.02. Gender, type of schooling and personal rating of the student were found to have a statistically significant association on comparison. A low degree of statistically insignificant negative correlation (r=-0.1) between age and empathy scores was found. Conclusions: The mean empathy scores recorded in our study are lower as compared to those obtained by Western studies. Aptitude assessment at the time of Bachelor of medicine and Bachelor of Surgery (MBBS) entry could improve the selection of students to those who possess more attributes necessary in a doctor. Orientation in empathy is also required for MBBS students as it is documented that clinical empathy level is amenable to change by empathy education. Males, government school students and very good and average to poor students need special attention to improve their empathy levels. Longitudinal empathy training could minimize the negativity of age on empathy levels in student.